The Effectiveness of Electronic Land Certificates in Ensuring Legal Certainty of Land Rights - Atikah, Novia (Semarang State University Undergraduate Law and Society Review, 2025)
This research examines the effectiveness of electronic land certificates in ensuring legal certainty of land rights in Pekalongan City. The digital transformation of land administration represents a strategic initiative by the government to improve public services, yet its implementation faces significant challenges. The study aims to compare the effectiveness of conventional and electronic certificates, identify supporting and inhibiting factors, and assess their impact on legal certainty and protection of land rights. Employing an empirical approach, data was collected through interviews with officials at the Pekalongan City Land Office, direct observations, and document analysis of relevant regulations including the 1960 Basic Agrarian Law, Government Regulation No. 24/1997, and Ministerial Regulation ATR/BPN No. 1/2021. Content analysis and normative interpretation were applied to analyze the data. The findings reveal that while electronic certificates offer advantages in security, accessibility, and administrative efficiency, their implementation remains suboptimal due to uneven technological infrastructure, low digital literacy among communities, and internal resistance from land office employees toward system changes. Challenges include risks of certificate duplication and data overlap, while opportunities lie in enhanced transparency of land services. The research concludes that certificate digitalization has not yet achieved full effectiveness due to structural, cultural, and institutional barriers. The study recommends developing digital infrastructure at regional levels, providing intensive training for land office staff, and conducting massive public outreach to optimize land digitalization as an instrument of agrarian reform and state administration modernization.